2003
DOI: 10.1021/es0303283
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Precipitation and Sorption of Elements during Mixing of River Water and Porewater in the Coeur d'Alene River Basin

Abstract: Reddish brown flocs form along the edge of the Coeur d'Alene River when porewater drains into river water during the annual lowering of water level in the basin. The precipitates are efficient scavengers of dissolved elements and have characteristics that may make metals associated with them bioavailable. This work characterizes the geochemistry of the porewater and models the formation and composition of the flocs. Porewater is slightly acidic, has suboxic to anoxic characteristics, tends to have higher alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 44 publications
(59 reference statements)
2
42
1
Order By: Relevance
“…The concentrations of heavy metals Ba, Pb, and Cd in pore water measured in this study are approximately two, six, and 36 times greater than concentrations reported by Balistrieri et al (2003). Sulfate and As concentrations are about five and 130 times lower, respectively, than those reported by Balistrieri et al (2003). Historical data (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) from the US Geological Survey database show a strong positive correlation in filtered and unfiltered samples (p<0.0001) between Pb and Zn and the redox active elements Fe and Mn.…”
Section: Aqueous Chemistrycontrasting
confidence: 68%
See 4 more Smart Citations
“…The concentrations of heavy metals Ba, Pb, and Cd in pore water measured in this study are approximately two, six, and 36 times greater than concentrations reported by Balistrieri et al (2003). Sulfate and As concentrations are about five and 130 times lower, respectively, than those reported by Balistrieri et al (2003). Historical data (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) from the US Geological Survey database show a strong positive correlation in filtered and unfiltered samples (p<0.0001) between Pb and Zn and the redox active elements Fe and Mn.…”
Section: Aqueous Chemistrycontrasting
confidence: 68%
“…These data are compared to analyses reported in Balistrieri et al (2003) and are within the range of historically observed measurements from the US Geological Survey database (monitoring site 12413860 near Harrison Idaho http://nwis.waterdata.usgs.gov/id/ nwis/qw). The concentrations of heavy metals Ba, Pb, and Cd in pore water measured in this study are approximately two, six, and 36 times greater than concentrations reported by Balistrieri et al (2003). Sulfate and As concentrations are about five and 130 times lower, respectively, than those reported by Balistrieri et al (2003).…”
Section: Aqueous Chemistrymentioning
confidence: 75%
See 3 more Smart Citations